An amorphous silicon carbide coating and a method for its production
Patent Information
- Application Number
- CN202611343943.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]本发明的目的在于,提供一种非晶碳化硅涂层及其制备方法,能够解决温度敏感基体及低温基体难以制备SiC涂层的问题,同时解决SiC陶瓷与金属间界面结合性差的问题,在不改变基体组织的情况下提高了基体与SiC涂层的结合力,并基于功率脉冲磁控溅射技术制备的SiC涂层为非晶涂层,因其缺乏晶界而表现出相对于晶态SiC更优异的抗氧化性、抗辐照性能及机械性能
本发明通过在基体上从内到外依次沉积打底层、过渡层和沉积层的方式,打底层通过更高的负偏压为溅射出的离子提供了快的加速度,使其可以更深的嵌入基体,增强基体界面的膜基结合力,再依次沉积过渡层和沉积层,通过设计脉宽对占空比进行调控,通过减少单个脉冲周期内的放电持续时间,使放电过程中具有更高的峰值能量,使被溅射离子具有更高的能量,从而显著提升涂层质量。沉积出的非晶涂层Si-C完全成键,同时涂层更均匀更致密,从而基于用高功率脉冲磁控溅射技术制备的非晶碳化硅涂层,可以精确控制涂层的形态、结构和厚度,且可以实现高致密涂层的制备,同时由于较低占空比高能量带来的原位结构弛豫现象,消除了结构不均匀性得到更均匀的非晶网络,在不改变基体组织的情况下提高了基体与SiC陶瓷涂层的结合力,具有更优异的综合力学性能,并在一定范围内随着占空比降低硬度先增加再降低,模量同样呈现先增加后降低的趋势,并使低占空比样品具有更高的H/E值及较高的H3/E2,制备的SiC涂层为非晶涂层,因其缺乏晶界而表现出相对于晶态SiC更优异的抗氧化性、抗辐照性能。
Smart Images

Figure CN122979845A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silicon carbide coating preparation technology, specifically relating to an amorphous silicon carbide coating and its preparation method. Background Technology
[0002] Silicon carbide (SiC) is an important wide-bandgap semiconductor material and structural ceramic material, due to the strong sp atoms between silicon and carbon atoms. 3 Hybridized covalent bonds endow SiC with high hardness, high elastic modulus, excellent high-temperature resistance, corrosion resistance, and radiation resistance, making it a promising candidate for applications in extreme environments. In the aerospace field, SiC-based composites, with their lightweight, high strength and toughness, and excellent high-temperature performance, are widely used in hot-end components of aero engines, significantly improving the engine's thrust-to-weight ratio and thermal efficiency, and effectively extending its service life. In the nuclear energy field, SiC is considered an ideal structural material for nuclear reactors due to its excellent resistance to neutron radiation, superior high-temperature stability, and self-healing ability against radiation damage. However, the inherent brittleness of SiC ceramics limits its application as a monolithic structural component. Therefore, depositing SiC as a coating on the substrate surface has become a strategically valuable technological approach to achieve perfect coordination between function and structure, transitioning from a single material to a functional SiC coating and broadening its application scope.
[0003] Existing methods for preparing SiC coatings include chemical vapor deposition (CVD), plasma spraying, electrodeposition, sol-gel methods, and physical vapor deposition (PVD). SiC coatings prepared by CVD form a dense SiO2 layer at high temperatures, effectively preventing oxygen diffusion and exhibiting excellent oxidation resistance. However, its high preparation temperature limits its application on heat-sensitive and low-temperature substrates. While plasma spraying and electrodeposition can achieve uniform deposition of complex shapes, the resulting coatings suffer from high porosity and poor film-substrate adhesion, directly affecting the final performance. Furthermore, silicon carbide coatings are mainly concentrated in crystalline silicon carbide; in friction applications, grain shedding can exacerbate abrasive wear. Simultaneously, grain boundaries are often preferential pathways for corrosion and electrochemical reactions. To overcome these inherent defects of crystalline coatings, researchers have been using magnetron sputtering technology in physical vapor deposition (PVD) to prepare amorphous or nanocrystalline SiC coatings at lower temperatures, aiming to obtain a denser, more uniform structure with fewer grain boundaries. However, the currently widely used radio frequency magnetron sputtering process is limited by the low ion energy, making it difficult to achieve complete bonding of Si-C. The prepared SiC coating has a large amount of free Si and free C, resulting in poor interfacial bonding between SiC ceramics and metals. Summary of the Invention
[0004] The purpose of this invention is to provide an amorphous silicon carbide coating and its preparation method, which can solve the problem of difficulty in preparing SiC coatings on temperature-sensitive substrates and low-temperature substrates, and at the same time solve the problem of poor interfacial bonding between SiC ceramics and metals. It improves the bonding force between the substrate and the SiC coating without changing the substrate structure. The SiC coating prepared based on power pulse magnetron sputtering technology is an amorphous coating, which exhibits superior oxidation resistance, radiation resistance and mechanical properties compared to crystalline SiC due to the lack of grain boundaries.
[0005] The present invention solves the above-mentioned technical problems through the following technical solutions.
[0006] The first objective of this invention is to provide a method for preparing an amorphous silicon carbide coating, comprising the following steps: A functional coating of amorphous silicon carbide is obtained by sequentially depositing an underlayer, a transition layer, and a deposition layer on a substrate from the inside out using pulsed magnetron sputtering under vacuum.
[0007] When depositing the underlayer, the matrix bias voltage is -100 to -500V; when depositing the transition layer, the matrix bias voltage is -400V to 0V; and when depositing the sedimentary layer, the matrix bias voltage is -300V to 0V. The bias voltage decreases sequentially from the three stages of depositing the underlayer, the transition layer, to the sedimentary layer.
[0008] When depositing the bottom layer, transition layer, and sedimentary layer, the duty cycle is 1% to 99%.
[0009] When depositing the underlayer and transition layer, the sputtering power is 20W to 1000W, and when depositing the deposition layer, the sputtering power is 1000W to 10000W.
[0010] Furthermore, before the bottom layer is built up, the vacuum is between 1×10 -5 ~9.9×10 -4 Between Pa, during the deposition of the underlayer, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the underlayer is 1nm to 1μm.
[0011] Furthermore, during the deposition of the transition layer, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the transition layer is 1nm to 5μm.
[0012] Furthermore, during the deposition process, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the underlayer is 50nm to 50μm.
[0013] Furthermore, the deposition of the underlayer, transition layer, and deposition layer is carried out under a nitrogen / argon mixed gas atmosphere, with an argon flow rate of 5 sccm to 50 sccm, a nitrogen flow rate of 0 sccm to 50 sccm, and a gas pressure of 0.02 Pa to 2.0 Pa.
[0014] Furthermore, the matrix is a metal matrix or a ceramic matrix.
[0015] Furthermore, before depositing the underlayer, the magnetron sputtering vacuum chamber is evacuated to a pressure below 9.9 × 10⁻⁶. -4 Pa, perform glow discharge sputtering cleaning on the substrate surface, introduce argon gas at a flow rate of 5 sccm to 50 sccm and a pressure of 0.02 Pa to 2.0 Pa, and apply a bias voltage of -100 V to -500 V to the substrate. The glow discharge cleaning time shall not be less than 5 minutes.
[0016] Furthermore, before deposition, the substrate was successively polished with 400#, 800#, 1500#, 2000#, and 3000# sandpaper, then polished with 0.5μm, 0.25μm, and 0.05μm diamond polishing agents and 0.02μm silicon oxide polishing agent, and finally ultrasonically cleaned with acetone and anhydrous ethanol for 5 to 15 minutes, and then dried.
[0017] A second objective of this invention is to provide an amorphous silicon carbide coating prepared using the above-described preparation method.
[0018] Compared with the prior art, the present invention has the following advantages: This invention utilizes a method of sequentially depositing an underlayer, a transition layer, and a deposition layer on a substrate from the inside out. The underlayer, through a higher negative bias voltage, provides a faster acceleration for the sputtered ions, allowing them to embed deeper into the substrate and enhancing the film-substrate adhesion at the substrate interface. Then, the transition layer and the deposition layer are deposited sequentially. By designing the pulse width to control the duty cycle, and reducing the discharge duration within a single pulse cycle, higher peak energy is achieved during the discharge process, resulting in higher energy for the sputtered ions and thus significantly improving the coating quality. The deposited amorphous coating exhibits complete Si-C bonding, resulting in a more uniform and denser coating. Therefore, the amorphous silicon carbide coating prepared using high-power pulsed magnetron sputtering technology allows for precise control of the coating's morphology, structure, and thickness, enabling the fabrication of highly dense coatings. Furthermore, the in-situ structural relaxation phenomenon caused by the high energy at a lower duty cycle eliminates structural inhomogeneities, resulting in a more uniform amorphous network. This improves the adhesion between the matrix and the SiC ceramic coating without altering the matrix microstructure, leading to superior overall mechanical properties. Within a certain range, the hardness initially increases and then decreases with decreasing duty cycle, while the modulus also shows a similar trend of initial increase followed by decrease. Additionally, the low duty cycle sample exhibits a higher H / E value and higher Hc. 3 / E 2The prepared SiC coating is an amorphous coating, which exhibits superior oxidation resistance and radiation resistance compared to crystalline SiC due to the lack of grain boundaries. Attached Figure Description
[0019] Figure 1 This is a cross-sectional morphology diagram of the amorphous SiC coating prepared in Example 1 of the present invention.
[0020] Figure 2 The images show the scratch SEM, EDS, and acoustic signal images of the amorphous SiC coating prepared in Example 1 of this invention. Figure 2 In the figure, (a) is the scan of the scratch and its EDS result, (b) is the magnified SEM result of the scratch coating peeling area in (a), (c) is the acoustic emission signal corresponding to the scratch in (a), and (d) is the magnified EDS result of the scratch coating peeling area in (a).
[0021] Figure 3 The images show the scratch SEM, EDS, and acoustic signal images of the amorphous SiC coating prepared in Example 2 of this invention.
[0022] Figure 4 The results are the nanomechanical test results of the coatings prepared in Examples 1 to 3 of this invention. Figure 4 In the figure, (a) represents the hardness and modulus of samples with different duty cycles, and (b) represents the hardness and modulus of samples with different duty cycles. H / E and H 3 / E 2 ratio. Detailed Implementation
[0023] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0025] This invention provides a method for preparing an amorphous silicon carbide coating, comprising the following steps: A functional coating of amorphous silicon carbide is obtained by sequentially depositing an underlayer, a transition layer, and a deposition layer on a substrate from the inside out using pulsed magnetron sputtering under vacuum.
[0026] Understandably, the substrate is mounted on the workpiece gantry within the vacuum chamber of the magnetron sputtering equipment. The SiC target can be attached to targets such as HiPIMS or RF targets. Before deposition, the magnetron sputtering equipment needs to be evacuated, and the magnetron sputtering vacuum chamber needs to be evacuated to a pressure below 9.9 × 10⁻⁶. -4 Pa, and then glow discharge cleaning is performed to remove impurities and oxide layers from the substrate surface and activate the substrate surface. Specifically, argon gas is introduced at a flow rate of 5 sccm to 50 sccm and a pressure of 0.02 Pa to 2.0 Pa. The substrate is subjected to a bias voltage of -100 V to -500 V, and the glow discharge cleaning time is not less than 5 min.
[0027] In this invention, the vacuum level is between 1×10⁻⁶ before the underlayer deposition. -5 ~9.9×10 -4 Between Pa and , a nitrogen / argon mixture is then introduced into the vacuum chamber. The argon flow rate is 5 sccm to 50 sccm, the nitrogen flow rate is 0 sccm to 50 sccm, and the pressure is 0.02 Pa to 2.0 Pa. During the underlayer deposition, the substrate bias voltage is -100 to -500 V; the sputtering power is 20 W to 1000 W. During the deposition of the substrate layer, the sputtering power is 1000 W to 10000 W, the sputtering frequency is 100 Hz to 5000 Hz, the pulse width is 5 μs to 500 μs, the duty cycle is 1% to 99%, and the underlayer thickness is 1 nm to 1 μm.
[0028] In this invention, a transition layer is deposited on the substrate while maintaining the flow rate and pressure of the nitrogen / argon mixed gas. When depositing the transition layer, the substrate bias voltage is -400V to 0V, the sputtering power is 20W to 1000W, and when depositing the substrate layer, the sputtering power is 1000W to 10000W, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, the duty cycle is 1% to 99%, and the thickness of the transition layer is 1nm to 5μm.
[0029] In this invention, a secondary deposition layer is deposited on the transition layer, maintaining the flow rate and pressure of the nitrogen / argon mixed gas. During deposition, the substrate bias voltage is -300V to 0V, the sputtering power is 1000W to 10000W, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, the duty cycle is 1% to 99%, and the thickness of the underlayer is 50nm to 50μm.
[0030] It is understandable that during the deposition of the transition layer, the transition layer can be deposited in stages by adjusting the substrate bias to make the transition layer more uniform and improve the film-substrate bonding.
[0031] It should be noted that the coating is applied in three stages from the inside out: the base layer, the transition layer, and the deposition layer. The bias voltage is decreased in each stage to improve the adhesion between the coating and the substrate.
[0032] The substrate can be a metallic or ceramic substrate. In this invention, the metallic substrate includes sheet materials and various tubular materials such as Zr, Cr, Al, and stainless steel, while the ceramic substrate can be Si, SiC, C / C composite materials, etc. It is understood that before deposition, the substrate is sequentially polished with 400#, 800#, 1500#, 2000#, and 3000# sandpaper, then sequentially polished with 0.5μm, 0.25μm, and 0.05μm diamond polishing agents and 0.02μm silicon dioxide polishing agent, and finally ultrasonically cleaned with acetone and anhydrous ethanol for 5-15 minutes, followed by drying.
[0033] When the substrate is a sheet (plate), the deposition rate is between 50 nm / h and 50 μm / h. When the substrate is tubular, the deposition rate of the SiC coating on the substrate is between 50 / π nm / h and 50 / π μm / h, achieved by rotating the substrate around its central axis.
[0034] This invention provides a method for preparing an amorphous silicon carbide coating on a substrate surface using high-power pulsed magnetron sputtering technology. The method involves depositing an underlayer, a transition layer, and a deposition layer sequentially from the inside out on the substrate. During the underlayer deposition process, a higher negative bias provides a faster acceleration for the sputtered ions, allowing them to embed deeper into the substrate and enhancing the film-substrate adhesion at the substrate interface. Furthermore, by designing the pulse width to control the duty cycle, under fixed discharge power conditions, reducing the discharge duration within a single pulse cycle results in higher peak energy during the discharge process, giving the sputtered ions higher energy and thus significantly improving the coating quality. The deposited amorphous Si-C coating exhibits complete bonding, resulting in a more uniform and denser coating. This allows for precise control of the morphology, structure, and thickness of the amorphous silicon carbide coating prepared using high-power pulsed magnetron sputtering technology, enabling the fabrication of highly dense coatings. Furthermore, the in-situ structural relaxation phenomenon caused by the low duty cycle and high energy eliminates structural inhomogeneities, resulting in a more uniform amorphous network. This solves the problem of preparing SiC coatings on temperature-sensitive and low-temperature substrates, and also addresses the issue of poor interfacial bonding between SiC ceramics and metals. Without altering the substrate microstructure, the adhesion between the substrate and the SiC ceramic coating is improved, leading to superior overall mechanical properties. Within a certain range, the hardness initially increases and then decreases with decreasing duty cycle, while the modulus also shows a similar trend of initial increase followed by decrease. This results in lower duty cycle samples exhibiting higher H / E values and higher Hc values. 3 / E 2The prepared SiC coating is an amorphous coating, which exhibits superior oxidation resistance and radiation resistance compared to crystalline SiC due to the lack of grain boundaries. Therefore, this invention can be used to prepare highly dense, high-bonding-strength amorphous silicon carbide functional coatings on thermosensitive or complex-shaped substrates at temperatures below 400 degrees Celsius, and amorphous SiC layers with different mechanical properties can be obtained by changing the duty cycle.
[0035] The following specific examples will provide further explanation.
[0036] Example 1 A method for preparing a 6% duty cycle amorphous SiC coating on the surface of a zirconium alloy tubular substrate using magnetron sputtering technology includes the following steps: Step 1: The Zr alloy tube is polished sequentially with 400#, 800#, 1500#, 2000#, and 3000# sandpaper, and then mechanically polished with 0.5μm, 0.25μm, and 0.05μm diamond polishing agents and 0.02μm silicon oxide polishing agent. Then, it is ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes and dried. The sample is then mounted on the workpiece gantry in the vacuum chamber of the magnetron sputtering equipment, and the SiC target is mounted on the target position connected to the HiPIMS power supply.
[0037] Step 2: Introduce argon gas into the vacuum chamber and perform glow discharge sputtering cleaning on the substrate surface. The bias voltage is -400V, and the sputtering time is 30 minutes.
[0038] Step 3: Open the SiC target and introduce argon gas with a purity of not less than 99.9% at a flow rate of 20 sccm and a working pressure of 0.1 Pa. Prepare the SiC substrate with a sputtering frequency of 2000 Hz, a pulse width of 30 μs, a duty cycle of 6%, a power of 1000 W, a substrate bias of -400 V, and a deposition thickness of 100 nm.
[0039] Step 4: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -300 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 30 μs, the duty cycle is 4%, and the power is 1500 W. Then, a 100 nm SiC transition layer is deposited on the SiC substrate. Step 5: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -100 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 30 μs, the duty cycle is 4%, and the power is 3500 W. A 1.3 μm SiC layer is then deposited on the SiC transition layer. This yields the amorphous SiC coating.
[0040] Example 2 A method for preparing a 4% duty cycle SiC coating on the surface of a zirconium alloy sheet substrate using magnetron sputtering technology includes the following steps: Step 1: The Zr alloy sheet was polished sequentially with 400#, 800#, 1500#, 2000#, and 3000# sandpaper, and mechanically polished sequentially with 0.5μm, 0.25μm, and 0.05μm diamond polishing agents and 0.02μm silicon oxide polishing agent. Then, it was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes in sequence and dried. The sample was then mounted on the workpiece gantry in the vacuum chamber of the magnetron sputtering equipment, and the SiC target was mounted on the target position connected to the HiPIMS power supply.
[0041] Step 2: Introduce argon gas into the vacuum chamber and perform glow discharge sputtering cleaning on the substrate surface. The bias voltage is -400V, and the sputtering time is 30 minutes.
[0042] Step 3: Open the SiC target and introduce argon gas with a purity of not less than 99.9% at a flow rate of 20 sccm and a working pressure of 0.1 Pa. Prepare the SiC substrate by sputtering at a frequency of 2000 Hz, a pulse width of 20 μs, a duty cycle of 4%, a power of 1000 W, a substrate bias of -400 V, and a deposition thickness of 100 nm.
[0043] Step 4: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -300 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 20 μs, the duty cycle is 4%, and the power is 1500 W. A 100 nm SiC transition layer is then deposited on the SiC substrate.
[0044] Step 5: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -200 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 20 μs, the duty cycle is 4%, and the power is 2000 W. Then, a 100 nm SiC transition layer 2 is deposited on the SiC transition layer 1.
[0045] Step 6: With a working gas pressure of 0.1 Pa, a bias voltage of -100 V applied to the substrate, a SiC target sputtering RF rate of 2000 Hz, a pulse width of 20 μs, a duty cycle of 4%, and a power of 3500 W, a 2 μm SiC layer is deposited on the SiC transition layer. This yields the amorphous SiC coating.
[0046] Example 3 A method for preparing an 8% duty cycle SiC coating on a Si sheet substrate using magnetron sputtering technology includes the following steps: Step 1: After mechanical polishing, the single crystal Si wafer is ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes in sequence and then dried. The sample is then mounted on the workpiece gantry in the vacuum chamber of the magnetron sputtering equipment, and the SiC target is mounted on the target position connected to the HiPIMS power supply.
[0047] Step 2: Introduce argon gas into the vacuum chamber and perform glow discharge sputtering cleaning on the substrate surface. The bias voltage is -400V, and the sputtering time is 30 minutes.
[0048] Step 3: Open the SiC target and introduce argon gas with a purity of not less than 99.9% at a flow rate of 25 sccm and a working pressure of 0.1 Pa. Prepare the SiC substrate by sputtering at a frequency of 2000 Hz, a pulse width of 40 μs, a duty cycle of 8%, a power of 1000 W, a substrate bias of -400 V, and a deposition thickness of ~100 nm.
[0049] Step 4: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -250 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 40 μs, the duty cycle is 8%, and the power is 2000 W. A 300 nm SiC transition layer is then deposited on the SiC substrate.
[0050] Step 5: The working gas pressure is 0.1 Pa, the bias voltage applied to the substrate is -100 V, the SiC target sputtering RF rate is 2000 Hz, the pulse width is 40 μs, the duty cycle is 8%, and the power is 3500 W. A 1.5 μm SiC layer is then deposited on the SiC transition layer. This yields the amorphous SiC coating.
[0051] The structure and performance of the SiC coatings prepared in Examples 1 to 3 and the comparative examples were tested, and the results are shown below.
[0052] Figure 1 This is a cross-sectional morphology diagram of the amorphous SiC coating prepared in Example 1 of the present invention. Figure 1 As shown, after depositing a SiC layer with a 6% duty cycle for 5 hours, the coating thickness was uniformly 1.58 μm.
[0053] Figure 2 The images show the scratch SEM, EDS, and acoustic signal images of the amorphous SiC coating prepared in Example 1 of this invention. Figure 2 In the figure, (a) shows the scan of the scratch and its EDS result, (b) shows the magnified SEM result of the scratch coating peeling area in (a), (c) shows the acoustic emission signal corresponding to the scratch in (a), and (d) shows the magnified EDS result of the scratch coating peeling area in (a). Figure 2 As shown, these scratches were generated by a linearly increasing progressive load at a constant loading rate of 100 N / min. When the load exceeded 10 N but was below 15 N, localized peeling of the coating occurred, but the scratch trajectory was intact, the edges were clear, and there was no nearby coating peeling. At the end of the scratch trajectory, no obvious cracks or peeling of the silicon carbide layer were observed, indicating that it has good interfacial adhesion strength with the substrate.
[0054] Figure 3The images show the SEM, EDS, and acoustic signal images of the scratches on the amorphous SiC coating prepared in Example 2 of this invention. Figure 3 As shown, these scratches were generated at a constant loading rate of 15 N / min through linearly increasing progressive loads (up to 15 N). When the load exceeded 5 N but was below 10 N, localized peeling of the 4% duty cycle deposited coating occurred, which perfectly coincided with the timing of the acoustic emission signal burst. As the continuous normal load increased from 10 N to 15 N, the acoustic emission signal exhibited dramatic fluctuations; the corresponding EDS distribution also confirmed that the Zr-4 substrate was clearly exposed in the delaminated region due to coating failure. The scratch tracks remained intact, with clear edges and no nearby coating peeling. At the end of the scratch tracks, no obvious cracks or peeling of the silicon carbide layer were observed, indicating good interfacial adhesion strength between it and the substrate.
[0055] Figure 4 The results are the nanomechanical test results of the coatings prepared in Examples 1 to 3 of this invention. Figure 4 In the figure, (a) represents the hardness and modulus of samples with different duty cycles, and (b) represents the hardness and modulus of samples with different duty cycles. H / E and H 3 / E 2 Ratio. For example... Figure 4 As shown, with decreasing duty cycle, the hardness increases from 18.758 GPa to 18.961 GPa, then decreases to 18.372 GPa; similarly, the elastic modulus increases from 180.925 GPa to 185.462 GPa before decreasing to 175.773 GPa. Therefore, the low duty cycle sample exhibits a higher H / E ratio and a relatively higher H3 / E2 ratio. This mechanical evolution is fundamentally dominated by the in-situ structural relaxation effect caused by high energy input at low duty cycles. This effect eliminates local structural inhomogeneities, forming a more uniform amorphous network.
[0056] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
[0057] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing an amorphous silicon carbide coating, characterized in that, Includes the following steps: A functional coating of amorphous silicon carbide is obtained by sequentially depositing an underlayer, a transition layer and a deposition layer on a substrate from the inside out under vacuum using pulsed magnetron sputtering. When depositing the underlayer, the matrix bias voltage is -100V to -500V; when depositing the transition layer, the matrix bias voltage is -400V to 0V; when depositing the sedimentary layer, the matrix bias voltage is -300V to 0V. The bias voltage decreases sequentially from the three stages of depositing the underlayer, the transition layer to the sedimentary layer. When depositing the sublayer, transition layer, and sedimentary layer, the duty cycle is 1% to 99%; When depositing the underlayer and transition layer, the sputtering power is 20W to 1000W, and when depositing the deposition layer, the sputtering power is 1000W to 10000W.
2. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, Before the bottom layer is built up, the vacuum is between 1×10 -5 ~9.9×10 -4 Between Pa, during the deposition of the underlayer, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the underlayer is 1nm to 1μm.
3. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, During the deposition of the transition layer, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the transition layer is 1nm to 5μm.
4. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, During the deposition process, the sputtering frequency is 100Hz to 5000Hz, the pulse width is 5μs to 500μs, and the thickness of the underlayer is 50nm to 50μm.
5. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, The deposition of the underlayer, transition layer, and deposition layer is carried out under a nitrogen / argon mixed gas atmosphere, with an argon flow rate of 5 sccm to 50 sccm, a nitrogen flow rate of 0 sccm to 50 sccm, and a gas pressure of 0.02 Pa to 2.0 Pa.
6. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, The matrix is a metal matrix or a ceramic matrix.
7. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, Before depositing the underlayer, the magnetron sputtering vacuum chamber is evacuated to a pressure below 9.9 × 10⁻⁶. -4 Pa, perform glow discharge sputtering cleaning on the substrate surface, introduce argon gas at a flow rate of 5 sccm to 50 sccm and a pressure of 0.02 Pa to 2.0 Pa, and apply a bias voltage of -100 V to -500 V to the substrate. The glow discharge cleaning time shall not be less than 5 minutes.
8. The method for preparing an amorphous silicon carbide coating according to claim 1, characterized in that, Before deposition, the substrate was successively polished with 400#, 800#, 1500#, 2000# and 3000# sandpaper, then polished with 0.5μm, 0.25μm and 0.05μm diamond polishing agent and 0.02μm silicon oxide polishing agent, respectively. Finally, it was ultrasonically cleaned with acetone and anhydrous ethanol for 5 min to 15 min, and then dried.
9. An amorphous silicon carbide coating, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.